Study of the delta-cp dependence of astrophysical neutrino oscillations (2017)
This work presents a formalism for computing the neutrino time evolution operator in the general case for when the neutrinos travel through a medium of varying density. This takes up Chapter 2. The following chapter studies the relevant considerations for when evolution of the neutrinos through the Earth is considered. This provides understanding of the important phenomena that will be taken into account in Chapter 4, for when time evolution through the Earth is taken to calculate the muon-track to shower ratio as function of delta-CP.These results are analysed in Chapter 5, where the behaviour of the obtained plots is studied and the feasibility of measuring delta-CP experimentally is explored. The concluding remarks of the thesis are summarised in Chapter 6.